2019
DOI: 10.3390/molecules24122197
|View full text |Cite
|
Sign up to set email alerts
|

It’s Only a Part of the Story: Analytical Investigation of the Inks and Dyes Used in the Privilegium Maius

Abstract: The Privilegium maius is one of the most famous and spectacular forgeries in medieval Europe. It is a set of charters made in the 14th century upon commitment by Duke Rudolf IV, a member of the Habsburg family, to elevate the rank and the prestige of his family. These five charters, now kept at the Österreichisches Staatsarchiv in Vienna, have been subjected to a thorough interdisciplinary study in order to shed light on its controversial story. The charters are composed of pergamenaceous documents bound to wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…including any other technology used to prepare the document. The following 64 articles [ [548] , [549] , [550] , [551] , [552] , [553] , [554] , [555] , [556] , [557] , [558] , [559] , [560] , [561] , [562] , [563] , [564] , [565] , [566] , [567] , [568] , [569] , [570] , [571] , [572] , [573] , [574] , [575] , [576] , [577] , [578] , [579] , [580] ] [ [581] , [582] , [583] , [584] , [585] , [586] , [587] , [588] , [589] , [590] , [591] , [592] , [593] , [594] , [595] , [596] , [597] , [598] , [599] , [600] , [601] , [602] , [603] , [604] , [605] , [606] , [607] , [608] , [609] , [610] , [611] ], combined with 17 presentations [...…”
Section: Forensic Document Examinationunclassified
See 1 more Smart Citation
“…including any other technology used to prepare the document. The following 64 articles [ [548] , [549] , [550] , [551] , [552] , [553] , [554] , [555] , [556] , [557] , [558] , [559] , [560] , [561] , [562] , [563] , [564] , [565] , [566] , [567] , [568] , [569] , [570] , [571] , [572] , [573] , [574] , [575] , [576] , [577] , [578] , [579] , [580] ] [ [581] , [582] , [583] , [584] , [585] , [586] , [587] , [588] , [589] , [590] , [591] , [592] , [593] , [594] , [595] , [596] , [597] , [598] , [599] , [600] , [601] , [602] , [603] , [604] , [605] , [606] , [607] , [608] , [609] , [610] , [611] ], combined with 17 presentations [...…”
Section: Forensic Document Examinationunclassified
“…Calà et al [ 594 ] identified possible forgeries in historical documents using non-destructive and micro-destructive methods. Studying mainly the ink and dyed threads on the Privilegium maius, the team used Fiber Optics Diffuse Reflectance Spectroscopy (FORS) analysis to distinguish the types of black ink present.…”
Section: Forensic Document Examinationmentioning
confidence: 99%
“…It is also worth noting the absence of the two anthraquinones anthrapurpurin and flavopurpurin which, according to recent works by Liu [33,34], provides evidence of the natural provenance of madder used to dye the embroidery: in fact these two compounds can be used as the markers for distinguishing between synthetic alizarin and natural alizarin from madder.…”
Section: Hplc-dad-ms Analysismentioning
confidence: 99%
“…Paper chromatography and thin layer chromatography (TLC) [5] have the advantage of simple and direct operation for routine analysis. Analytical methods, including high-performance liquid chromatography (HPLC), [6,7] capillary electrophoresis (CE), [8,9] laser desorption ionization (LDI), [10,11] and matrixassisted laser desorption/ionization (MALDI), [12,13] secondary ion mass spectrometry (SIMS), [14,15] and electrospray ionization mass spectrometry (ESI-MS), [16] have also been used to identify the dyes and pigments in ink samples.…”
Section: Introductionmentioning
confidence: 99%